1995
DOI: 10.1109/77.402757
|View full text |Cite
|
Sign up to set email alerts
|

High temperature superconducting bearings for lunar telescope mounts

Abstract: Abstract--A telescope to be installed on the lunar surface in the near futere mast work in a cold and dusty vacuum environment fur long periods without on site human maintenance.. To track stars, the drive mechanism must be capable of exceedingly fine steps and repeatability.Further We report on the first prototype I-ITS bearing module built at the University of Houston in collaboration with Chert to be assembled as an azimuth mount for a levitated lunar telescope, see Fig. 1. II. LUNAR BEARING REQUIREMENTSTo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Other applications for HTS bearings in which a cryogenic environment already exists include cryogenic turbine flow metres [161] and cryocoolers for space [29] or terrestrial use. Another application for which a cryogenic environment naturally exists is the use of HTS bearings in a lunar telescope [162]. The drive mechanism of the telescope must be capable of exceedingly fine steps and repeatability, and it must survive and operate in the cold temperatures of the lunar night.…”
Section: Applicationsmentioning
confidence: 99%
“…Other applications for HTS bearings in which a cryogenic environment already exists include cryogenic turbine flow metres [161] and cryocoolers for space [29] or terrestrial use. Another application for which a cryogenic environment naturally exists is the use of HTS bearings in a lunar telescope [162]. The drive mechanism of the telescope must be capable of exceedingly fine steps and repeatability, and it must survive and operate in the cold temperatures of the lunar night.…”
Section: Applicationsmentioning
confidence: 99%
“…The three main components are (1) a stator magnet, fixed with respect to ground, (2) a rotor magnet, to which the rotating liquid-mirror telescope is to be attached, and (3) high-temperature superconductor (Lamb et al 1995) stabilizer where indicated in Figure 3. The magnets are rare-earth permanent magnets, made of an alloy of neodymium, iron, and boron.…”
Section: Bearingsmentioning
confidence: 99%
“…Another application for which a cryogenic environment naturally exists is the use of HTS bearings in a lunar telescope. 62 In this case, the drive mechanism must be capable of exceedingly fine steps and repeatability and survive and operate in the extremely low temperatures of the lunar night. Prototype HTS bearings for such a telescope have been constructed and tested.…”
Section: Applicationsmentioning
confidence: 99%